Importance index, failure probability and reability of the component of distribution aerial line (Publicaciones en Ciencias y Tecnología, 2009)
A significant number of power interruptions in electric distribution systems are caused by component failures of airlines, namely that actions could be implemented to reduce them improve the quality of service provided. The aim of this study is to determine the importance indices, failure probability and reliability of the components of overhead power distribution lines of 13.8, 24 and 34.5 kV, of the ENELBAR and CADAFE, which serve the design future maintenance plans. The methodology consists of analyzing the statistics of failures occurred in the period from 2006 to 2008 to determine these variables, using the probabilistic software ReliaSoft Weibull + + 7 R. The results were analyzed a total of 969 failures and shows that the conductor and the connectors are the components with the importance indices and failure probability highest in all three studies. We conclude that maintenance plans can design this component so as to guide the reduction of resources for service failures.
Keywords: Failure probability; importance indices; reliability